The role of bacteriotherapeutic drugs under stress - Starovoitova, Svitlana (My University, 2018)
There is a functional connection between the gastrointestinal tract (GIT) and the central nervous system (CNS) of the host organism. This relationship is bi-directional and includes anatomical relationships, such as the vagus nerve and humoral components, including the immune and hypothalamic-pituitary-adrenal system. Recently, there is more and more experimental evidence that another key player in this interaction is the intestinal microbiota.
Keywords: probiotics; stress; microbiota; пробіотики; стрес; мікробіота; кафедра біотехнології і мікробіології; пробиотики; стресс; микробиота